2020
DOI: 10.3390/ma13061382
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Inaccuracy and Variability of Material and Selected Technological Factors on Physical and Mechanical Properties of Fresh Masonry Mortars and Plasters

Abstract: The article presented the analysis of the impact that various kinds of technological inaccuracies have on the properties of fresh masonry mortars and plasters. Analyzed were the inaccuracies in dosing of mortar components, namely, water, lime, and air-entraining plasticizing admixture (APA) (±10% of mass), and the effect of variable technological conditions, namely, different mixing intensity (fast, slow, normal) and temperature (5 • C, 20 • C, and 35 • C) during first 72 h after mixing. The impact of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
4
0
1
Order By: Relevance
“…Admixtures are supplied as powders, the typically used low dosages being 0.3–1.5% of the weight of the cement. The researchers have established [ 11 , 12 , 13 , 14 ] that the introduction of additives improves workability and lowers the water demand of the mix, confers air entrainment, or adds waterproofing qualities. These changes have the potential to decrease cracking through improvements in the paste–aggregate bond and to increase the strength of hardened mortars.…”
Section: Introductionmentioning
confidence: 99%
“…Admixtures are supplied as powders, the typically used low dosages being 0.3–1.5% of the weight of the cement. The researchers have established [ 11 , 12 , 13 , 14 ] that the introduction of additives improves workability and lowers the water demand of the mix, confers air entrainment, or adds waterproofing qualities. These changes have the potential to decrease cracking through improvements in the paste–aggregate bond and to increase the strength of hardened mortars.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, lime mortars were used; however, currently, cement mortars and cement–lime mortars are most popular in traditionally erected constructions [ 1 ]. In the literature, much attention was paid to the research of traditional mortars and their varieties, types of binder, additives, and admixtures and their influence on physical and mechanical properties [ 3 ] or durability [ 4 ]. Much mortar research concerns aggregate and fillers [ 5 ], and replacing cement with other materials, including waste [ 5 , 6 , 7 , 8 , 9 , 10 ], organic materials [ 11 ], and pozzolans [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, assessing the differences in the use of both is important both from a theoretical and practical point of view, as it may affect the process of construction. Some researchers paid attention to plasticizing admixtures for mortars in their works [ 3 , 23 , 34 ]. Lenart [ 23 ] obtained results that showed that air-entraining and plasticizing admixtures improved workability but decreased compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…Current research indicates that depending on the type of admixture used, there may be great variability in their properties' results [9], [10], even with compounds with the same chemical name [11]. Viscosity, molar mass and/or nature and quantity of chemical substitution groups can be responsible for these variations [12].…”
Section: Introductionmentioning
confidence: 99%